Proceedings of the 12th International Conference on Mobile and Ubiquitous Multimedia 2013
DOI: 10.1145/2541831.2541872
|View full text |Cite
|
Sign up to set email alerts
|

Seek'N'Share

Abstract: We present a location-based collaborative mobile learning platform called Seek'N'Share. It is comprised of a Web-based learning assignment editor and a mobile application for exploring and capturing multimedia content in the field. The editor enables drag-and-drop creation of learning tasks, areas and points of interest using an intuitive Web interface. Assignments are accessed with an Android application that uses location information to provide content and tasks to learners as they explore the environment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A fitting example is the student who said she did not know that she was resident in a neighborhood that was racially segregated in the past (East Austin). This led us to suggest that rather than local Versión pdf para imprimir desde http://revistas.urosario.edu.co/index.php/disertaciones ESTUDIOS 70 DISERTACIONES history, which is current theme in several location-based learning projects (Heimonen et al, 2013) segregation and gentrification were found as useful topics to be studied through location-based learning. This is due to their spatial characteristics and capacity to enable students to explore the physical world by understanding the urban embodiment of the topic discussed in the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fitting example is the student who said she did not know that she was resident in a neighborhood that was racially segregated in the past (East Austin). This led us to suggest that rather than local Versión pdf para imprimir desde http://revistas.urosario.edu.co/index.php/disertaciones ESTUDIOS 70 DISERTACIONES history, which is current theme in several location-based learning projects (Heimonen et al, 2013) segregation and gentrification were found as useful topics to be studied through location-based learning. This is due to their spatial characteristics and capacity to enable students to explore the physical world by understanding the urban embodiment of the topic discussed in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…The "environment" is mostly outdoors Randell, Phelps & Rogers, 2003;Rogers et al, 2004) but it may also be indoor, such as in museums (Vavoula et al, 2009), or a combination of both (Rogers et al, 2005). "Mobile learning" is usually used to refer to the inclusion of mobile phones in the classroom (Cabrera et al, 2005;Grasso & Roselli 2005;Hsi & Fait, 2005), while "location-based learning" started being used around and after the widespread adoption of smartphones for learning (Chou & Chanlin, 2014;Heimonen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this aspect of locative media is described by (Willis and Cheverst, 2011) To date, locative media has been exploited in various domains but most notably: storytelling (Procyk & Neustaedter 2014), literature (Løvlie, 2012), games (Procyk & Neustaedter 2014;Bell et al 2009), city exploration relating to cultural heritage and history (Cheverst et al, 2002;Reid et al, 2005;Nisi et al 2006 andFitzGerald et al 2012) and mobile learning (Heimonen et al 2013).…”
Section: Background and Related Work The Growth And Scope Of Locativementioning
confidence: 99%